Pengetahuan, Sikap, Kebiasaan Merokok, Aktifitas Fisik, dan Kepatuhan Minum Obat Berhubungan Dengan Pengedalian Hipertensi - Jaya Hia, Trisman; Simanjorang, Asyiah; J. Hadi, Anto (Window of Health : Jurnal Kesehatan, 2020)
Hypertension is the highest cause of death and illness. History of hypertension along with unhealthy lifestyles such as smoking, physical activity and medication adherence. This study aims to determine the factors associated with controlling hypertension in the Working Area of ​​UPT Puskesmas Padang Bulan Kota Medan. This type of research is quantitative with a cross sectional study design. Population and sample are patients who come to visit and have their health checked by sampling technique using accidental sampling as many 100 people and univariate, bivariate and multivariate data analysis. The results of research that have been carried out obtained that there is a significant relationship of knowledge (p = 0.006), attitudes (p = 0.011), smoking habits (p = 0.018), physical activity (p = 0.017), compliance with taking medication (p = 0,000) with controlling hypertension. Compliance with medication drinks is most dominant with hypertension control (Sig 0.001 and Exp 24.048). The conclusion is that there is a relationship between knowledge, attitude, smoking habits, physical activity, medication adherence with hypertension control. It is expected that the puskesmas make prevention efforts, or overcome the problem of hypertension by conducting hypertension counseling / counseling to patients.